Early Life Manipulations of the Nonapeptide System Alter Pair Maintenance Behaviors and Neural Activity in Adult Male Zebra Finches - Baran, Nicole M.; Tomaszycki, Michelle L.; Adkins-Regan, Elizabeth (Frontiers in Behavioral Neuroscience, 2016)
Adult zebra finches (T. guttata) form socially monogamous pair bonds characterized by proximity, vocal communication, and contact behaviors. In this experiment, we tested whether manipulations of the nonapeptide hormone arginine vasotocin (AVT, avian homologue of vasopressin) and the V1a receptor (V1aR) early in life altered species-typical pairing behavior in adult zebra finches of both sexes. Although there was no effect of treatment on the tendency to pair in either sex, males in different treatments exhibited profoundly different profiles of pair maintenance behavior. Following a brief separation, AVT-treated males were highly affiliative with their female partner but sang very little compared to Controls. In contrast, males treated with a V1aR antagonist sang significantly less than Controls, but did not differ in affiliation. These effects on behavior in males were also reflected in changes in the expression of V1aR and immediate early gene activity in three brain regions known to be involved in pairing behavior in birds: the medial amygdala, medial bed nucleus of the stria terminalis, and the lateral septum. AVT males had higher V1aR expression in the medial amygdala than both Control and antagonist-treated males and immediate early gene activity of V1aR neurons in the medial amygdala was positively correlated with affiliation. Antagonist treated males showed decreased activity in the medial amygdala. In addition, there was a negative correlation between the activity of V1aR cells in the medial bed nucleus of the stria terminalis and singing. Treatment also affected the expression of V1aR and activity in the lateral septum, but this was not correlated with any behaviors measured. These results provide evidence that AVT and V1aR play developmental roles in specific pair maintenance behaviors and the neural substrate underlying these behaviors in a bird.